(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The present study was conducted in Department of Anatomy, NIIMS and SMSR, Greater Noida out of which 200 subjects (100 males and 100 females) between age group of 18-35 years. Two measurements, the facial length, Facial breadth were taken by using Digital Vernier caliper. To calculate the facial Index in Males and Females & measure the facial length and facial breadth of the subject. It was concluded that the Percentage of Very long face Shape (43%) is larger than long face shape (24%), Round face shape (23%), Broad face shape (10%) & Very broad face shape (2%) in females. In males the Percentage of Very long face Shape (41%) is also larger than long face shape (36%), Round face shape (16%), Broad face shape (9%) and Very broad shape (2%).